Analisis Penerapan Sanksi Pidana Nomor 37/Pid.B/2022/PN Pdp Tentang Kealpaan Pemasangan Arus Listrik yang Menyebabkan Kematian - Musnandar, Fitri Ramadhani; Z, Yenny Fitri (Innovative: Journal Of Social Science Research, 2024)
This research provides an overview of criminal acts of negligence or neglect. A criminal act can occur not only because of the will, deliberate intention to carry out or ignore a prohibited act, but there are also criminal acts that occur due to carelessness, carelessness or negligence. To determine whether a person who commits a criminal act can be held accountable for committing a criminal act if it is proven that they have made a mistake. Formulation of the problem raised 1) How is the regulation of criminal acts of negligence that cause death in Indonesia, 2) Analysis of the decision in criminal case Number 37/Pid.B/2022/PN Pdp. The method used in this research is normative research, where this research can be carried out by means of library research, so that it can answer the problem formulation according to the author's title. Based on the research results, it was found that Criminal Decision Number 37/Pid.B/2022/PN Pdp was a criminal act of negligence in installing an electric current which resulted in death, and the Defendant's actions had fulfilled the elements of Article 359 of the Law. The Criminal Code is the element of the person, the element of negligence or negligence that causes another person to die